UPAYA TOKOH AGAMA DALAM PELAKSANAAN WALIMATUL ‘URSY AGAR SESUAI DENGAN AJARAN ISLAM DI DESA TEBAT MONOK KECAMATAN KEPAHIANG KABUPATEN KEPAHIANG - Ali Akbar (IAIN Bengkulu, 2018)
The formulation of this study is: First, how the position of religious leaders in the community of Tebat Village Monok? Secondly, what is the efforts of religious leaders in the cultivation of religious values at the wedding party (Walimah al-’Ursy) in Tebat Monok village Kepahiang district? This type of research is descriptive research with sociological juridical ap- proach.Data collection uses interviews, observations and documentation. This research concludes that: First, the position of religious leaders in the Village Tebat Monok Kepahiang District is a leader of religious worship activities, train people in religious practice and become a community advisor.. Secondly, the efforts made by religious leaders in Tebat Monok Village are: Establish a da’wah approach by giving an enlightenment to the public on various occasions such as in a lecture or gather- ing of citizens on how to implement walimahan by paying close attention to the aspects of religious teaching, using a personal approach to Community by giving advice and feedback about how it should be done so that the party is not redundant, does not cause vice and benefit to the people but still has the meaning for those who wish